Screencast-O-Matic Application Assisted Project Learning Model: A Case Study Of IAIN Langsa FTIK Student Creativity - Jelita, Jelita; Anggreni, Fenny (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2023)
System chandes in education influenced by industrial revolution 4.0. Several changes were made by utilizing several applications that support each learning process. One use of the Screencast-O Matic (SOM) application in lectures by combining PowerPoint with videos from students' faces so that they can improve their quality. This study aims to determine student creativity and the influence of the Screencast-O Matic (SOM) assisted project learning model on the creativity of FTIK IAIN Langsa students. This study uses associative research/causality with a quantitative approach. The population used in this study were all 6th-semester students of FTIK IAIN Langsa who took the quantitative research methodology course, totaling 293 students. The research sample was obtained by a purposive technique using the Slovin formula. Based on this formula, 75 students were obtained as a research sample with a tolerance limit of 10%. The instrument was a closed questionnaire with 15 questions and an observation sheet. The data were analyzed using SPSS version 20. The results showed that student creativity was 78.00 with high criteria. There was a significant influence of the use of the SOM applicationassisted project learning model on the creativity of FTIK IAIN Langsa students.